Experimental study on modeling of shallow soil landslide reinforced by micropiles - Li, Ming; Li, Pengju; Li, Dongdong (Frontiers in Earth Science, 2024)
The practical application of micropiles in landslide reinforcement and prevention advanced before theoretical research, significantly limiting their application and promotion. To determine the damage patterns and stress distribution of micropiles during sliding failure in reinforced shallow landslides, three sets of physical modeling tests were performed. These tests examined the stability of shallow soil slopes with and without micropiles, including single-row and three-row configurations. During the tests, the foot displacement of the landslide, the top displacement of the micropiles, and the strain within the micropiles were monitored throughout the loading process. Following the tests, the landslide was excavated to observe the damage patterns in the micropiles. The experimental results showed that the pile-soil composite structure formed by three rows of micropiles, together with the soil between them, significantly improved the stability of the landslide and demonstrated effective anti-sliding effects. The stress distribution curve of the micropile was inversely S-shaped, with the peak stress located near the sliding surface. Within the micropile group, the first row exhibited the highest stress, and the micropiles nearest to the free face experienced the greatest displacement. Through the micropile-reinforced landslide tests, we identified three stages in the slope’s sliding damage process and the stress distribution pattern of the micropiles. The research findings offer valuable insights into the anti-sliding mechanism of micropiles, which can guide design and construction.